Study of the genetic and phenotypic variation among wild and cultivated clary sages provides interesting avenues for breeding programs of a perfume, medicinal and aromatic plant. - Camille Chalvin (Public Library of Science (PLoS), 2021)
A road-map of the genetic and phenotypic diversities in both crops and their wild related species can help identifying valuable genetic resources for further crop breeding. The clary sage (Salvia sclarea L.), a perfume, medicinal and aromatic plant, is used for sclareol production and ornamental purposes. Despite its wide use in the field of cosmetics, the phenotypic and genetic diversity of wild and cultivated clary sages remains to be explored. We characterized the genetic and phenotypic variation of a collection of six wild S. sclarea populations from Croatia, sampled along an altitudinal gradient, and, of populations of three S. sclarea cultivars. We showed low level of genetic diversity for the two S. sclarea traditional cultivars used for essential oil production and for ornamental purposes, respectively. In contrast, a recent cultivar resulting from new breeding methods, which involve hybridizations among several genotypes rather than traditional recurrent selection and self-crosses over time, showed high genetic diversity. We also observed a marked phenotypic differentiation for the ornamental clary sage compared with other cultivated and wild clary sages. Instead, the two cultivars used for essential oil production, a traditional and a recent one, respectively, were not phenotypically differentiated from the wild Croatian populations. Our results also featured some wild populations with high sclareol content and early-flowering phenotypes as good candidates for future breeding programs. This study opens up perspectives for basic research aiming at understanding the impact of breeding methods on clary sage evolution, and highlights interesting avenues for clary breeding programs.